Carrageenan-based hard capsule properties at different drying time - Mohd Aiman, Hamdan; S. S., Lakashmi; Khairatun Najwa, Mohd Amin; Fatmawati, Adam (IOP Publishing, 2020)
Shelf life of biocomposite can be monitored by many preservation methods such as drying of biocomposite. Upon drying, water molecule will be removed due to evaporation to surrounding and effect the biocomposite quality, chemical and mechanical properties. Over drying process will lead to the reduction of chemical and mechanical properties of biocomposite. In this work, determination of the best drying time for carrageenan biocomposite hard capsule was performed and compared with commercial hard capsules which are gelatine (GHC) and hydroxypropyl methylcellulose (HPMC). Carrageenan was mixed with crosslinker, cellulose nanocrystal (CNC) and toughening agent at various drying time. The colloid solution was dipped using size "1" dipping bar and dried at 60 0C for various drying time from 40 to 60 minutes in an oven. The carrageenan hard capsule (CHC) was analysed for weight variation, functional group and capsule hardness test. The result showed that increasing the drying time decreased the properties of the CHC. The CHC had higher hydroxyl group absorbance area in comparison to GHC and HPMC. Meanwhile, the GHC had the highest hardness load followed by HPMC and CHC. Material hardening occurred in CHC biocomposite upon increasing drying time thus lead to material shrinkage and water loss from the sample.